Socioeconomic Factors and Their Influence on The Consumptive Behaviour of Senior High School Students - Pane, Nirwani; Busyra, Nur (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
This research is based on the current phenomenon that adolescents are easily influenced by consumptive behaviour. This is based on the fear that teenagers will decrease their social status or self-esteem, which causes irrational consumption patterns to continue. This research uses quantitative methods that focus on data that can be measured or numerical to test a hypothesis. Data collection techniques with observation and questionnaires. The population in this study were 224 Adiluhur High School students and a sample of 144 using the data sampling technique. The tests used in this study were the Chi Quadrat test and regression linearity test. Pearson product-moment (PPM) correlation test, T-test, and determination coefficient test. The results of the research analysis of the correlation between social class and the consumptive behaviour of high school teenage students obtained at 0.000 there is a sig value <0.005 and received the results of tcount> Ttable obtained by 10.866> 1.1655 then H0 is rejected, Ha is accepted, meaning there is a positive and significant relationship between social class and wasteful behaviour. It is known that the R Square value is 0.454, so it can be concluded that the relationship between social class and consumptive behaviour is 45.4%. Known Pearson correlation variable social class and consumptive behaviour of 0.674, this value has a strong level of relationship.Keywords: Social class, consumptive behaviour, high school students.